Modularization vs. Innovation. Issue 1 (1st March 2014) - Fiorineschi, Lorenzo; Rissone, Paolo; Rotini, Federico
Abstract : This paper argues the relationship between modularity and product innovation. The work is based on the assumption that in order to become an innovation, a novel product has to be successfully diffused into the marketplace. Modularity can give rise to a series of parameters related to commercial success; however, there is not a well-defined relationship between modularity and product innovativeness. The aim of the paper is to analyse the logic of the most acknowledged modularization methods in-order to understand how they can really influence product success, and then, part of product innovativeness.